2019
DOI: 10.1007/s10842-019-00303-6
|View full text |Cite
|
Sign up to set email alerts
|

One Bad Turn Deserves Another: How Terrorism Sustains the Addiction to Capital Flight in Africa

Abstract: This inquiry assesses if terrorism sustains the capital flight trap and whether the relationship is affected by varying the levels of governance and globalisation. The empirical evidence is based on interactive Generalised Method of Moments with data from 37 African countries for the period 1996-2010. The followings are established. (1) Evidence of a capital flight trap is apparent because past values of capital flight have a positive effect on future values of capital flight. (2) Terrorism sustains the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…There is a paradox between the increasing capital flight from Africa and the substantially documented need of finance for the continent's growing ambitions. On the one hand, the continent is a net creditor to the rest of the world because her capital outflows substantially surpass corresponding capital inflows (Boyce & Ndikumana, 2012a;Asongu et al, 2019). For instance, according to the narrative, thirty-three countries in sub-Saharan Africa (SSA) lost approximately 814 billion US Dollars (in constant of 2010 terms) between 1970 and 2010, to capital flight.…”
Section: Introductionmentioning
confidence: 99%
“…There is a paradox between the increasing capital flight from Africa and the substantially documented need of finance for the continent's growing ambitions. On the one hand, the continent is a net creditor to the rest of the world because her capital outflows substantially surpass corresponding capital inflows (Boyce & Ndikumana, 2012a;Asongu et al, 2019). For instance, according to the narrative, thirty-three countries in sub-Saharan Africa (SSA) lost approximately 814 billion US Dollars (in constant of 2010 terms) between 1970 and 2010, to capital flight.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of socio-political and institutional factors, such as military expenditure, terrorism, political instability, corruption control on capital flight were considered in the studies of Efobi and Asongu (2016), Asongu and Amankwah-Amoah (2018), Asongu et al (2019), Osei-Assibey et al ( 2017), and Asongu and Nnanna (2020), respectively. Generally, they provided evidence of the effects of these non-economic factors on capital flight in Sub-Saharan African countries at one time or the other.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The functional form is given below; + + + The strategy of GMM, which will be used here, is adapted from (Simplice A. Asongu, et al, 2019). In step 2 on analysis, the impact of capital flight is checked on the economic performance of developing countries, and for that GLS (Generalized Least Square) technique is used; functional form is given below; The current account balance is a sum of net exports goods and services, net primary income, and net secondary income.…”
Section: Methodsmentioning
confidence: 99%
“…some studies have shown it as a most disturbing element for the investors, and they shift their assets abroad by any means (Efobi & Asongu, 2016), (Simplice A. Asongu, et al, 2019) and (Hyder, Akram, & Padda, 2015). Third, the reason is to analyze the association of Economic freedom and capital flight.…”
Section: Literature Reviewmentioning
confidence: 99%